2005
DOI: 10.1186/1741-7015-3-12
|View full text |Cite
|
Sign up to set email alerts
|

Public beliefs about treatment and outcome of mental disorders: a comparison of Australia and Japan

Abstract: Background: Surveys of the public in a number of countries have shown poor recognition of mental disorders and beliefs about treatment that often diverge from those of health professionals. This lack of mental health literacy can limit the optimal use of treatment services. Australia and Japan are countries with very different mental health care systems, with Japan emphasising hospital care and Australia more oriented to community care. Japan is also more collectivist and Australia more individualist in values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
253
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(278 citation statements)
references
References 31 publications
(31 reference statements)
18
253
5
Order By: Relevance
“…18 More than one third of the students reported that the patients with depression will have a better outcome, if treated, whereas only one third of the students believed that patients with psychosis will have good outcome if treated. This finding is convergent with the results by A F Jorm et al 9,12 and Matthias C Angermeyer et al 19 who reported that the majority of respondents considered that full recovery followed by problems reoccurring would be the most likely outcome for all case vignettes, other than the psychosis case vignette, for which partial recovery with problems reoccurring was considered to be the most likely outcome. Student's belief about possible outcomes for those with mental disorders reflects a less optimistic view especially for psychosis which may be due to the lack of knowledge of causes and risk factors of mental disorders.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…18 More than one third of the students reported that the patients with depression will have a better outcome, if treated, whereas only one third of the students believed that patients with psychosis will have good outcome if treated. This finding is convergent with the results by A F Jorm et al 9,12 and Matthias C Angermeyer et al 19 who reported that the majority of respondents considered that full recovery followed by problems reoccurring would be the most likely outcome for all case vignettes, other than the psychosis case vignette, for which partial recovery with problems reoccurring was considered to be the most likely outcome. Student's belief about possible outcomes for those with mental disorders reflects a less optimistic view especially for psychosis which may be due to the lack of knowledge of causes and risk factors of mental disorders.…”
Section: Discussionsupporting
confidence: 82%
“…The inheritance or genetic cause was not reported to be a reason for depression, but for psychosis over one third endorsed genetic cause, which is consistent with the findings from Bourget et al 15 , Matthias C et al 19 and Jorm et al 9 This can be explained that depression may be considered by the students as an commonest expected mental disorder which occurs in all communities because of routine life activities. Additionally, the present study findings were contradictory to the findings of Yoshibumi Nakane et al 12 and Harshal Salve et al 25 that evil spirits, virus or infection and allergy can be the causative factors. The present study shows even though the overall awareness of the students about the risk factors for developing depression and psychosis was low means that understanding of the students about the risk factors for psychosis was apparently poorer than for depression.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, the present study could not replicate such a finding. This may be associated with the study by Jorm et al (2005) comparing Japanese and Australian participants, while the present study compared American and Japanese individuals. However, we believe that this inconsistency is more likely associated with a developmental issue.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, rather than seeking professional help, they may tend to talk to non-professionals. In addition, Jorm et al (2005) found a national difference for talking to friends/family between Japanese and Australian participants. Japanese participants tended to talk to their friends and families more than Australian participants.…”
Section: Discussionmentioning
confidence: 99%